Interleukin (IL)‐9/IL‐9R axis drives γδ T cells activation in psoriatic arthritis patients. (21st October 2016) - Guggino, G.; Ciccia, F.; Di Liberto, D.; Lo Pizzo, M.; Ruscitti, P.; Cipriani, P.; Ferrante, A.; Sireci, G.; Dieli, F.; Fourniè, J. J.; Giacomelli, R.; Triolo, G.
Summary: Cytokines such as tumour necrosis factor (TNF)‐α, interleukin (IL)‐12, interferon (IFN)‐γ, IL‐23 and, more recently, IL‐9, have been implicated in the initiation/maintenance of inflammation in psoriasis and psoriatic arthritis (PsA). In the present study we aimed to characterize the role of γδ T cells in peripheral blood and synovial fluid of PsA patients and to investigate their response to in‐vitro stimulation with antigen or cytokines (IL‐9 and IL‐23). γδ T cells isolated from peripheral blood mononuclear cells and synovial fluid were analysed by flow cytometry to evaluate the phenotype and cytokine production. IL‐23R and IL‐9R gene expression were also evaluated by reverse transcription–polymerase chain reaction (RT–PCR). Peripheral blood mononuclear cells (PBMC), sorted γδ T cells and γδ cell lines were also stimulated in vitro with isopentenyl pyrophosphate (IPP), recombinant IL‐9 or recombinant IL‐23. Our results show an expansion of γδ T cells with a predominant effector memory phenotype in peripheral blood and synovium of untreated PsA patients, which reverses significantly after treatment with anti‐TNF‐α or anti‐IL‐12/IL‐23R monoclonal antibodies (mAbs). Moreover, in PsA patients γδ T cells activation is driven prevalently by IL‐9/IL‐9R interaction, and not only by IL‐23/IL‐23R. Together these findings indicate γδ T cells and IL‐9 as new players in the pathogenesis of PsA. Abstract : IL‐9/IL‐9R axis drives gamma delta T cells activation in psoriatic arthritis patients